Cardioprotection by polysaccharide sulfate against ischemia/ reperfusion injury in isolated rat hearts - Yang Ying; Hu Shen-jiang; Li Liang; Chen Guo-ping (Acta Pharmacologica Sinica, 2016)
Aim: Polysaccharide sulfate (PSS) is a new type of heparinoid synthesized with alginic acid as the basic material and then by chemical introduction of effective groups. Although PSS is successfully applied in ischemic cardio-cerebrovascular disease, its effect on cardiac function after ischemia/reperfusion (I/R) injury has previously not been investigated. The aim of the present study was to investigate whether PSS can protect the heart from I/R injury and the underlying mechanism of protection. Methods: Isolated rat hearts were perfused (Langendorff) and subjected to 20 min global ischemia followed by 60 min reperfusion with Kreb’s Henseleit solution or PSS (0.3–100 mg/L). Myocardial contractile function was continuously recorded. Creatine kinase (CK) and lactate dehydrogenase (LDH) leakage were measured. Tumor necrosis factor-α (TNF-α) expression in cardiomyocytes was investigated. Western blot analysis for extracellular regulated kinases (ERKs), c-jun aminoterminal kinase (JNKs) and p38 mitogen-activated protein kinase (MAPK) activity was performed. Results: After I/R, cardiac contractility decreased, CK and LDH levels increased in the coronary effluent, and TNF-α expression increased in cardiomyocytes. PSS administration at concentrations of 1–30 mg/L improved cardiac contractility, reduced CK and LDH release and inhibited TNF-α production. Phosphorylated-p38MAPK (p-p38MAPK) and p-p54/p46-JNK increased in I/R rat hearts but diminished in PSS (1–30 mg/L) treated hearts. P-p44/p42-ERK levels were unchanged. In contrast, high concentrations of PSS (100 mg/L) had adverse effects that caused a worsening of heart function. Conclusion: PSS has dose-dependent cardioprotective effects on the rat heart after I/R injury. The beneficial effects may be mediated through normalization of the activity of p38 MAPK and JNK pathways as well as controlling the level of TNF-α expression.